Influence of the Crystal Structure on the Luminescence Properties of Mixed Eu,La-(1,10-Phenanthroline) Complexes - Yang, Ting-Hai
A series of europium Eu- and La-doped complexes with two different crystal structures, namely, EuxLa1-x(phen)(2)(NO3)(3) [phen = 1,10-phenanthroline, x = 1.0 (1), 0.88 (2), 0.73 (3), and 0.52 (4)] and {[EuxLa1-x(phen)(2)(H2O)(2)(NO3)(2)](NO3)2(phen)(H2O)} [x = 0.28 (5) and 0.0 (6)], were synthesized in aqueous solution by using different Eu/La ratios.The complexes were characterized by single-crystal and powder X-ray diffraction, Fourier transform infrared spectroscopy, elemental analysis, thermogravimetry, and scanning electron microscopy. Compounds 1-4 and 5, 6 were obtained for Eu/La molar ratios higher than 5:5 and smaller than 3:7, respectively. The photoluminescence properties of these compounds depend on the crystal structure, which is determined by the Eu/La reactant ratio. Complexes 1-4 exhibit a quantum efficiency ( = 55%) and quantum yield (q = 31%) higher than 5 ( = 23% and q = 6%). The photophysical properties assessed by using the LUMPAC software are in good accord with the experimental values, particularly, the calculated (26%) and measured emission quantum yields (31%; excitation at the ligands at 255 nm).